The consequences of human actions on risks for infectious diseases: A review - Lindahl, Johanna F.; Grace, Delia (Informa UK Limited, 2015)
The human population is growing, requiring more space for food production, and needing more animals to feed it. Emerging infectious diseases are increasing, causing losses in both human and animal lives, as well as large costs to society. Many factors are contributing to disease emergence, including climate change, globalization and urbanization, and most of these factors are to some extent caused by humans. Pathogens may be more or less prone to emergence in themselves, and rapidly mutating viruses are more common among the emerging pathogens. The climate-sensitive vector-borne diseases are likely to be emerging due to climate changes and environmental changes, such as increased irrigation. This review lists the factors within pathogens that make them prone to emergence, and the modes of transmission that are affected. The anthropogenic changes contributing to disease emergence are described, as well as how they directly and indirectly cause either increased numbers of susceptible or exposed individuals, or cause increased infectivity. Many actions may have multiple direct or indirect effects, and it may be difficult to assess what the consequences may be. In addition, most anthropogenic drivers are related to desired activities, such as logging, irrigation, trade, and travelling, which the society is requiring. It is important to research more about the indirect and direct effects of the different actions to understand both the benefits and the risks.